(NsOLOW)QÆÃWÆ sLAWNOMU (B- (NsLOWO(B. (NsERÆQ LISTÆWOK DO (B187-(NOÆ RÆ^NICÆ `RÆQ fEDXKOWI^A (B/s)E - (NbUNQK(B, (Nw(B.s ((NwALENTINA(B)s; (NbROZINSXKIJ(B, (Nm(B. (Nf(B.s ((NmIHAJLO fEDOROWI^(B)s; (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (Nw)QÆÃRE(B, (Na(B.s)E ((NaNATOLX(B)s; (NdEM^ENKO(B, (Nw(B. (Ng(B.s ((Nw)QÆTALÆJ gRIGOROWI^(B)s)E; (NdOBRQNSXKIJ(B, (Na(B. (Nm(B.s ((NaNATOL)QÆJ mIKOLAJOWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2021)
(NkOMPLEKT LIST)QÆWOK (B"(NsOLOWÆÃWÆ sLAWNOMU sLOWO(B" (NWIJ[OW DRUKOM U (B"(NwIDAWNI^OMU DOMÆ (B"(NrODOWÆD(B". (NdO WIDANNQ WKL@^ENO WÆR[Æ(B-(NPRISWQTI `RÆÃWÆ fEDXKOWI^U (B20-(NTI POETÆW bUKOWINI(B. (NsERED NIH (B- (NWÆR[Æ WIKLADA^ÆW TA WIPUSKNIKÆW ~ERNÆWECXKOGO UNÆWERSITETU(B. s)E
(NpRO)QÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNI TA AWTORÆW PRISWQTs)E
Keywords: (NfEDXKOWI^(B, (N`R)QÆJ aDALXBERTOWI^(B,s)E -- 1834-1888 (NRR(B.s; (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E